Self-Perceived Job Performance as a Mediator of the Effects of Academic Satisfaction and Quality on Loyalty - Lovemore Chikazhe; Charles Makanyeza (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Globally, there is increased customer mobility and competition within the higher education sector. As such, university management and administration practices should consider academic satisfaction, quality and loyalty as important factors to influence graduate job performance. The study was conducted to see if self-perceived job performance had a role in mediating the effect of academic satisfaction and perceived academic quality on academic loyalty. Data was collected from 714 respondents using a cross-sectional survey. The covariance-based structural equation modelling was used to test the hypotheses. According to the study results, self-perceived job performance partially mediates the eff ect of both academic satisfaction and academic quality on academic loyalty. The study fi ndings emphasise the importance of graduate quality and satisfaction in influencing loyalty. Thus, the higher education sector should take cognisance of self-perceived job performance as this also influences academic loyalty.